Loan Loss Provisions Determinants: Evidence from Indonesian Banks - Gunawan, Vania Pradipta (2013)
Loan loss provision is an account consisting of money set aside by banks’ managers to cover potential losses. This paper seeks to examine the determinants of loan loss provisions in Indonesian banking system over the period of 2006-2011 with regard to banks’ efficiency. Efficiency is estimated in the first part of the study using Stochastic Frontier Approach distance function. It is found that Indonesian banks are 88 per cent efficient. The Global Financial Crisis in 2008 affected the banking efficiency through contagion effect. In the second part of the study, efficiency is one of the variables that are tested against loan loss provisions. Generalized Method of Moments (GMM) Estimator method is used in the analysis. The result suggests Indonesian banks income smooth through loan loss provisions. Macroeconomic variables are found to be insignificant to the loan loss provisioning decision whereas non-performing loans have very strong coefficient, indicating that managers take into account non-performing loans when making decisions about loan loss provisions. Moreover, efficiency is a vital part in loan loss provisioning decision; hence failure to incorporate it in loan loss provisions study may cause the model to be biased.